Success or Failure in the City? Social Mobility and Rural-Urban Migration in Nineteenth- and Early-Twentieth-Century Groningen, the Netherlands - Richard Paping; Jacek Pawlowski (Historical Life Course Studies)
This article studies the relation between rural-urban migration and the upward and downward social mobility of different social groups from the perspective of the sending countryside and not of the receiving city. It utilizes two datasets regarding people born in the Groningen clay soil region (the Netherlands). By applying a revised version of HISCLASS for social stratification, it compares the social mobility of urban migrants with those staying in the countryside. Analysis of both databases shows distinct social differences in rural-urban migration, with children from non-agrarian rural elite families moving very frequently to a city; whereas, children from farmers and unskilled (farm) labourers were much less attracted by urban centres, despite restricted job opportunities in agriculture. Children from lower managers, skilled and lower-skilled workers in industry and services took an intermediate position. For all social groups (except for children of farmers), male urban migrants had on average a better social mobility performance than rural stayers, whereas for females the differences were rather limited. Children of unskilled workers, who rarely went to large cities, were far more successful than rural stayers. This suggests a positive selection. For Groningen, the findings oppose the pessimistic view of nineteenth and early-twentieth century rural-urban migrants mainly being pushed to the city by local circumstances, although their social opportunities in the countryside were indeed limited. The detailed database shows also that even a temporary movement to the city resulted on average in an improved social mobility performance, an indication that urban migrants of nearly all social backgrounds often accrued extra human capital during their stay in a large city.